Pertanggungjawaban Pidana terhadap Turut Serta melakukan Aborsi (Analisis Putusan Nomor: 252/Pid.B/2012/PN.Plp dan Putusan Nomor: 124/Pid.Sus/2014/PN.Liw) - Surya Hamdani (Jurnal SOMASI (Sosial Humaniora Komunikasi), 2020)
Based on positive law in Indonesia, the Criminal Code itself regulates abortion problems Article 299, Article 346 to Article 349, while Law No.36 of 2009 concerning Health regulates the problem of abortion Article 75 , 76, 77 and 194. In connection with the criminal act of inclusion regulated in Article 55 and Article 56 of the Criminal Code. Criminal responsibility for a criminal act of participating in abortion, in imposing a sentence the judge must fulfill a sense of justice for all parties, for that before imposing a verdict, the judge must pay attention to the aspect of justice. 252 / Pid.B / 2012 / PN.Plp, the author does not agree that the Judge decides with the Criminal Code, the author agrees with the Judge No. 124 / Pid.Sus / 2014 / PN.Liw, in which the Judge decided using Law No. 36 of 2009 concerning Health, because our country adheres to the principle of lex specialis derogat legi generali.